2009
DOI: 10.1002/casp.1029
|View full text |Cite
|
Sign up to set email alerts
|

National identity and international giving: Irish adults' accounts of charitable behaviour

Abstract: Research on helping behaviour has emphasized the importance of the group and particularly the nation in establishing the norms and boundaries of emergency helping. Less attention has been paid to the role of the national group in longer-term routine helping such as charitable giving. This is particularly important given recent research on intergroup helping which points to the impact of power relations on willingness of national groups to give and receive aid. The present research examines people's accounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…We will finish by highlighting three areas where future work to develop the analysis presented here is needed. First, another well‐established predictor of helping behaviour is national identification (Lay, González, & Cortés, ; Stevenson & Manning, ). During disasters, an increase, or a heightened salience, in national identification can occur (Gabrielsen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We will finish by highlighting three areas where future work to develop the analysis presented here is needed. First, another well‐established predictor of helping behaviour is national identification (Lay, González, & Cortés, ; Stevenson & Manning, ). During disasters, an increase, or a heightened salience, in national identification can occur (Gabrielsen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…When primed with a European identity, as opposed to a British identity, students showed an increased willingness to help in response to European disasters, but not to South American disasters. Similarly, Irish students cited national identity as one base from which decisions about help giving were made, and expressed a preference towards helping fellow Irish citizens before giving help to those abroad (Stevenson & Manning, 2010), and students in New Zealand preferred helping their own ingroup members before giving help to others (Dalton, Madden, Chamberlain, Carr, & Lyons, 2008). Additionally, people who feel stronger place attachment to their home or nation (e.g., Lewicka, 2011) may be more likely to take action in response to a disaster (Scannell & Gifford, 2017;Tagliacozzo, 2015).…”
Section: Helping After Natural Disastersmentioning
confidence: 99%
“…Elsewhere, it has been argued by Hall, Jones, Andrews and Cridland (2013) that many donors prefer the notion of helping local charities because it offers them the chance to contribute to their own communities, and they can view the impact first hand and can be more confident that the money will not be wasted on marketing or administrative work. Indeed, Stevenson and Manning (2010) have suggested that donors may potentially perceive local charities as using donations more wisely.…”
Section: What Motivates People To Donate To Charity?mentioning
confidence: 99%
“…For example, in Australia, negative attitudes towards offering ODA to Indonesia were partly motivated by fears that it may one day pose a military threat (Hull, 1988). It has also been argued that countries are perceived less worthy of donations if political leaders in said countries are seen as the cause of the problem (Radley & Kennedy, 1992) or if the country was perceived powerful and wealthy enough to resolve problems itself (Stevenson & Manning, 2010). For example, the UK's recent decision to cut ODA to India followed intense media criticism for allocating resources to a country that funded its own space programme (Riley-Smith, 2016).…”
Section: What Motivates People To Donate To Charity?mentioning
confidence: 99%
See 1 more Smart Citation